Genetic diversity and structure of Silver fir (Abies alba Mill.) at the south-eastern limit of its distribution range - Maria Teodosiu; Georgeta Mihai; Barbara Fussi; Elena Ciocîrlan (Annals of Forest Research, 2020)
In the Romanian Carpathians, Silver fir covers about 5% of the forest area and is the second most important conifer species. Although there are a number of genetic studies concerning the distribution of genetic diversity of Abies alba in Europe, populations from the south-eastern limit of the distribution range have been studied less. The aim of the present study was to assess the genetic diversity and differentiation in 36 silver fir populations along the Carpathian Mountains in Romania, using seven microsatellites loci. High levels of genetic diversity (He = 0.779 to 0.834 and AR = 11.61 to 14.93) were found in all populations. Eastern Carpathians populations show higher levels of diversity, both in allelic richness and expected heterozygosity and higher degrees of genetic differentiation compared to southern populations. Bayesian clustering analysis revealed the existence of two genetically distinct groups for silver fir populations, one larger cluster which comprises the Inner Eastern Carpathians, Curvature Carpathians, South Carpathians and the Banat Mountains and the second cluster contained most of the North and Outer Eastern Carpathians population. Both AMOVA and Barrier analysis supported genetic differentiation among geographical provenance regions. The high genetic diversity of silver fir populations from the eastern limit of its distribution provide high potential to mitigate the negative effects of climate warming being valuable genetic resources in the context of global change. The distribution pattern of genetic variation at local, regional and country scale could and should be considered for the preservation of the forest genetic resources.